Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.18869/acadpub.irjns.1.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Pituitary Adenoma and Suprasellar Meningioma: A Coincidence or Causation Effect? Report of Two Cases and Review of Literature

Abstract: Background and Importance:The coexistence of pituitary adenoma and another type of brain tumor is a very rare clinical scenario. Even though such a presentation can be an incidental event but the possible pathogenesis of coexistence of different lesions in the sella and suprasellar region has not yet been elucidated. Case Presentation: Two cases of concomitant sellar and suprasellar region tumors are reported. A 37-year-old lady with Prolactinoma and a suprasellar meningioma and a 42-year-old Acromegalic man w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Even though meningiomas and PAs are among the most common types of brain tumors -15-25% and 10-23%, respectively -the coexistence of both is a rare clinical scenario. (MORTAZAVI et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though meningiomas and PAs are among the most common types of brain tumors -15-25% and 10-23%, respectively -the coexistence of both is a rare clinical scenario. (MORTAZAVI et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a possible mechanism that may explain the growth of a meningioma due to GH-secreting PA, inducing arachnoid cap cells transformation into a meningioma. (MAIURI et al, 2005;MORTAZAVI et al, 2015;THEODROS et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is known to play a role in the appearance of intracranial tumors, but in cases such as ours, without prior exposition to radiotherapy, the origin is still unclear. Some authors suggest that it may happen by sheer chance, whereas others describe theories that may explain this association [ 8 , 10 ]. Suzuki et al suggest an involvement of the activation of signaling pathways for the receptor tyrosine kinases [ 12 ], and Friend et al showed that meningioma may express GH and IGF1 receptors [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al suggest an involvement of the activation of signaling pathways for the receptor tyrosine kinases [ 12 ], and Friend et al showed that meningioma may express GH and IGF1 receptors [ 13 ]. Although there are cases described in the literature of an association of meningioma with functioning and nonfunctioning pituitary adenomas, in the case of functioning adenomas, GH-producing varieties seem to predominate [ 9 , 10 , 14 ]. It remains to be seen whether GH itself or an overexpression of IGF1 receptors in these tumors induces a transformation into a meningioma.…”
Section: Discussionmentioning
confidence: 99%